A novel external catheter fixation method for chemotherapy using inferior epigastric arterial catheterization for cervical cancer. (12th May 2014) - Chen, Bo‐Lin; Li, Jie; Chen, Yong‐Yi; Tang, Xin‐Hui; Li, Xu‐Ying; Lin, Xiao‐Ping; Yang, Nong; Sui, Hong‐yin; Ye, Sha; Huang, Jing
Abstract : The aim of this randomized controlled study was to investigate the effects of a novel external catheter fixation method for chemotherapy using inferior epigastric arterial catheterization for cervical cancer.Patients diagnosed with cervical cancer were randomly divided into a control group ( n  = 32) and a treatment group ( n  = 33). Patients in the control group underwent a traditional fixation method using a haemostat, elastic band and abdominal bandage. Patients in the treatment group underwent an improved fixation method using an indwelling needle and membrane cover. We used a visual analogue scale (VAS) to evaluate each patient's comfort score and also recorded the incidence of needlestick injury and the length of injection time in each group. The VAS scores measured before and after chemotherapy in the treatment group were lower than in the control group. The incidence of needlestick injury in the treatment group was significantly lower than in the control group. The length of injection time in treatment group was significantly lower than in the control group. Compared with the traditional fixation method, the improved fixation method not only increased patient comfort but also reduced both the risk of needlestick injury and the length of injection time. This improved technique deserves increased clinical use.